1972
DOI: 10.3382/ps.0510738
|View full text |Cite
|
Sign up to set email alerts
|

Fat Absorption by the Very Young Chick

Abstract: Intestinal absorption of corn oil and beef tallow was studied in White Leghorn male chicks during the periods of 2 to 7 and 8 to 15 days of age. Absorption of both fats was less at the earlier age. The corrected absorbability of corn oil increased from 84 to 95%; that of beef tallow from 40 to 79%. With both dietary fats, the greatest amount of fat appeared in the excreta at 5 and 7 days of age and then decreased rapidly within a 2-day period. Absorbability values for corn oil and tallow during the 8 to 15 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
3

Year Published

1984
1984
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 9 publications
2
27
1
3
Order By: Relevance
“…As seen in Table 5, the required heat by tom turkey poults for the first week, under the given conditions, was calculated as 5544 W. However, there may be an advantage in providing supplementary heat to poults up to three weeks of age since they have not fully feathered, and their digestive system is not fully developed until 2 -3 weeks of age (Carew et al, 1972;North, 1984;Chen & Chiang, 2005). The heat increment of digestion is considerably lower in early life of poults due to incomplete development of the digestive system.…”
Section: Resultsmentioning
confidence: 99%
“…As seen in Table 5, the required heat by tom turkey poults for the first week, under the given conditions, was calculated as 5544 W. However, there may be an advantage in providing supplementary heat to poults up to three weeks of age since they have not fully feathered, and their digestive system is not fully developed until 2 -3 weeks of age (Carew et al, 1972;North, 1984;Chen & Chiang, 2005). The heat increment of digestion is considerably lower in early life of poults due to incomplete development of the digestive system.…”
Section: Resultsmentioning
confidence: 99%
“…The final composition of body fat is a pondered average among the fat produced endogenously from glucose, the quantity and composition of the fatty acids in the diet and the fat resulting from catabolism through β-oxidation (Ajuyah et al, 1991;Ferreira, 1999, Sanz et al, 2000b. Carew et al (1972) evaluated the absorption of corn oil and tallow in light male birds and observed that absorption of both fats was lower in younger birds. The capability to absorb corn oil increased from 84 to 95% from the first to the second week of age and absorption of tallow has increased from 40 to 79%.…”
Section: Lipid Absorptionmentioning
confidence: 99%
“…The physiological capacity of birds during the first post-hatching days limits fat absorption (Carew et al, 1972), and the limited fat digestion seems to be caused by insufficient secretion of bile salts and lipase (Krogdahl et al, 1985). Fat digestibility in chicks is 6% lower than that of adult roosters (Freitas et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in the proportion of saturated fatty acids in broiler diets causes weight gain depression and worse feed conversion ratio, as well as reductions in fat and fatty acids digestibility and energy metabolizability (Zollitsch et al, 1997;Dänicke et al, 2000). On the other hand, diets with high polyunsaturated fatty acid content promote lower body fat deposition (Crespo & Esteve-Garcia, 2002).The physiological capacity of birds during the first post-hatching days limits fat absorption (Carew et al, 1972), and the limited fat digestion seems to be caused by insufficient secretion of bile salts and lipase (Krogdahl et al, 1985). Fat digestibility in chicks is 6% lower than that of adult roosters (Freitas et al, 2005).…”
mentioning
confidence: 99%